Land Areas Management for Development of Tourism Different Types - SHAIMERDENOVA, Aigul; NURPEISSOV, Madi; AKHMETOVA, Kamshat; GARKUSHINA, Valentina (Journal of Environmental Management and Tourism, 2023)
This paper discusses the importance of the use of land resources for the development of tourism and recreational activities. The study of economic mechanisms of nature management stimulates interest in various forms of tourism, such as ecotourism, agrotourism, forest tourism. The expansion of the tourism industry, combined with a decrease in international tourist flows, leads to an increase in the number of specially protected natural areas. Land management is a system of measures aimed at compliance with land legislation, regulation of land relations and ensuring the rational use and conservation of land resources. The influence of factors connected with natural and cultural features of tourist places influences the development of land resources. In this paper, some researches are conducted to analyze how an efficient land management can stimulate different types of tourism.